Donovanosis, - Walter Belda Junior (Sociedade Brasileira de Dermatologia, 2020)
Abstract Donovanosis is a chronic, progressive, and indolent bacterial disease that affects the skin and mucous membranes of the genital and perigenital regions, often associated with sexual transmission, and with low infectivity. The malignant transformation of donovanosis lesions occurs exceptionally, as is usually seen in long-term ulcerations.